The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/gps.5524
|View full text |Cite
|
Sign up to set email alerts
|

Is loneliness associated with mild cognitive impairment in low‐ and middle‐income countries?

Abstract: Background Loneliness may be a risk factor for mild cognitive impairment but studies on this topic are scarce, particularly from low‐ and middle‐income countries (LMICs). Therefore, the aim of the present study was to investigate the association between loneliness and mild cognitive impairment (MCI) in six LMICs (China, Ghana, India, Mexico, Russia and South Africa). Methods Cross‐sectional, community‐based, nationally representative data from the WHO Study on global AGEing and adult health (SAGE) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
2
19
2
Order By: Relevance
“…Although these attributes are part of Cornwell and Waite’s SD measure, the study did not include the aspect of PI. A study conducted in low- and middle-income countries such as China, Ghana, India, Mexico, Russia and South Africa found that PI is significantly associated with MCI in individuals who are 65 years or older but not for those who are younger [ 19 ]. This study indicates a significant association between PI and MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Although these attributes are part of Cornwell and Waite’s SD measure, the study did not include the aspect of PI. A study conducted in low- and middle-income countries such as China, Ghana, India, Mexico, Russia and South Africa found that PI is significantly associated with MCI in individuals who are 65 years or older but not for those who are younger [ 19 ]. This study indicates a significant association between PI and MCI.…”
Section: Introductionmentioning
confidence: 99%
“…At present, direct research on loneliness and cognitive frailty is lacking. Some studies have demonstrated that loneliness is associated with cognitive impairment and frailty [ 18 , 19 , 48 ], reflecting the relationship between loneliness and cognitive frailty from the side. Loneliness has a high prevalence in people with low physical activity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the Chinese community-dwelling elderly, loneliness is a robust factor for cognitive impairment and frailty [ 18 ]. The results of a study involving middle-aged and elderly people in several low- and middle-income countries illustrated that loneliness is related to mild cognitive impairment [ 19 ]. The study suggested that reducing the incidence of loneliness in the population can maintain cognitive function and prevent the occurrence of dementia [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Smith et al . [ 28 ] shows that loneliness is associated with MCI in low and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%